2020
DOI: 10.1002/cam4.3621
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine inhibits the metastatic potential of ovarian cancer by blocking NaV1.5‐mediated EMT and FAK/Paxillin signaling pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Lidocaine is a local anesthetic drug derived from cocaine, and widely used in clinical application such as anti-bacteria, anti-inflammation, local skin anesthesia and so on ( Caracas et al, 2009 ; Adler et al, 2017 ; Cizmarikova et al, 2020 ). An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer ( Gao et al, 2018 ; Khan et al, 2019 ; Liu et al, 2021 ). For example, it was reported that intravenous infusion of lidocaine during operation was associated with improved overall survival of patients with pancreatic cancer ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine is a local anesthetic drug derived from cocaine, and widely used in clinical application such as anti-bacteria, anti-inflammation, local skin anesthesia and so on ( Caracas et al, 2009 ; Adler et al, 2017 ; Cizmarikova et al, 2020 ). An increasing number of evidences have demonstrated that lidocaine could affect the development of multiple tumors including ovarian and breast cancer ( Gao et al, 2018 ; Khan et al, 2019 ; Liu et al, 2021 ). For example, it was reported that intravenous infusion of lidocaine during operation was associated with improved overall survival of patients with pancreatic cancer ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gao and colleagues suggested that the administration of lidocaine could enhance the apoptosis of breast cancer cells caused by cisplatin, as well as alleviating their metastasis in vivo ( Gao et al, 2018 ). Moreover, lidocaine could also suppress the growth and metastasis of ovarian cancer ( Liu et al, 2021 ). However, whether ferroptosis is involved in the function of lidocaine in breast and ovarian cancer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the local anesthetics, retrospective studies have revealed that the use of these drugs for regional anesthesia during perioperative period reduced the recurrence rate of patients with breast cancer [46]. In keeping with this, in vitro experiments demonstrated that bupivacaine and lidocaine inhibited OC cells proliferation and metastasis by blocking Nav1.5, confirming their role as potential anticancer agents [47,48]. The multi-effects of lidocaine were also confirmed in vivo, by using murine syngeneic OC (ID8) model.…”
Section: Figure 1 Ion Channels Expression In Ovarian Cancer (Oc)mentioning
confidence: 77%
“…The multi-effects of lidocaine were also confirmed in vivo, by using murine syngeneic OC (ID8) model. The molecular mechanism by which lidocaine hampers OC malignancy was recently studied by Liu and collaborators, who demonstrated that lidocaine binding to Nav1.5 blocked the activation of FAK/Paxillin signaling pathway, inhibiting proliferation and metastasis, and decreased cisplatin resistance of OC cells [48]. However, it should be noted that these compounds might elicit their anticancer effects also through mechanisms other than VGSC inhibition.…”
Section: Figure 1 Ion Channels Expression In Ovarian Cancer (Oc)mentioning
confidence: 99%
See 1 more Smart Citation